Characteristics of Traumatic Optic Neuropathy (TON) Cases Diagnosed at Cicendo Eye Hospital in 2022-2024 - Irsyad, Cri; Kartika, Antonia (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2025)
ABSTRACT Introduction: Traumatic Optic Neuropathy (TON) is uncommon, with an overall incidence of 0,7-2,5%, and yet significantly vision threatening. Characteristics of TON cases are of great aid in basing diagnosis, research, and therapy, and are documented in lengths in developed nations such as Canada and UK. This study aims to paint a picture of TON cases in Indonesia, especially Cicendo Eye Hospital. Methods: Descriptive data are retrospectively collected from Electronic Medical Record (EMR) of Cicendo Eye Hospital. The data is collected from Diagnosed cases of TON from 2022-2024, amounting to 147 cases. Result: There are 147 diagnosed cases of TON in Cicendo eye hospital from 2022-2024, age of TON patients averages 31,7 ± 16.0, with 79,6% are of male gender, etiology of TON are traffic related trauma (61.8%), occupation related (15.3%), violence related (4.1%), and others (22.9%). Most cases (88.4%) received therapy after 24 hours of onset of trauma. Cases have varied initial visual acuity, ranging from no light perception (18.4%), light perception (8.2%), hand movement (17.7%), finger counting (21.1%), and better(20.4%). Management of TON includes oral citicoline alone(60.5%), with oral corticosteroid (18.4%), or with intravenous corticosteroid (21.1%). Conclusion: Within the 147 TON cases in Cicendo eye hospital from 2022-2024, TON patients are of age 31,7 ± 16.0, mostly male (79.6%), related to traffic accident (61.8%), evaluated 24 hours after onset (88.4%), have visual acuity for finger counting (21.1%), and treated with oral citicoline alone (60.5%).